2002
DOI: 10.2458/azu_jrm_v55i2_reece
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of prairie sandreed rhizome development

Abstract: Multiple generations of rhizome-connected tillers stabilize soils and produce measurable amounts of herbage on sandy rangeland throughout the world. However, little is known about the dynamics of rhizome development in these clonal plant species. Seasonal relationships between foliar characteristics and rhizomes of prairie sandreed [Calamovilfa longifolia (Hook) Scribn.] were examined on sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The apparent lack of effect of a dry spring on tiller emergence is consistent with a concurrent study at GSL in which rate of prairie sandreed tiller emergence and tiller number were poorly correlated with short-and long-term precipitation totals (Hendrickson et al 2000). Competitive effects of western ragweed that occurred after 10 July may have been linked to epic events of tiller mortality that are common in rhizomatous graminoids during the growing season (Callaghan 1976;de Kroon et al 1992;Reece et al 2002). For example, Reece et al (2002) found that under relatively dry conditions, densities of prairie sandreed tillers declined 25%-64% during July or August.…”
Section: Effects Of Western Ragweed Removal On Associated Speciessupporting
confidence: 66%
See 4 more Smart Citations
“…The apparent lack of effect of a dry spring on tiller emergence is consistent with a concurrent study at GSL in which rate of prairie sandreed tiller emergence and tiller number were poorly correlated with short-and long-term precipitation totals (Hendrickson et al 2000). Competitive effects of western ragweed that occurred after 10 July may have been linked to epic events of tiller mortality that are common in rhizomatous graminoids during the growing season (Callaghan 1976;de Kroon et al 1992;Reece et al 2002). For example, Reece et al (2002) found that under relatively dry conditions, densities of prairie sandreed tillers declined 25%-64% during July or August.…”
Section: Effects Of Western Ragweed Removal On Associated Speciessupporting
confidence: 66%
“…However, total organic reserves of the grass species in dormant-season grazed paddocks were similar to nongrazed paddocks, indicating that drought-induced increases in western ragweed were primarily the result of reduced basal area of grasses (Reece et al 2002), rather than vigor.…”
Section: Effects Of Associated Species Removal On Western Ragweedmentioning
confidence: 96%
See 3 more Smart Citations